2007
DOI: 10.1002/bdra.20347
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular abnormalities in Folr1 knockout mice and folate rescue

Abstract: Our observations suggest that the beneficial effect of folic acid for congenital heart defects might be mediated via its impact on neural crest cells and by gene regulation of signaling pathways involved in the development of the pharyngeal arches and the secondary heart field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 74 publications
1
43
0
Order By: Relevance
“…24 Thus, further studies will be of interest to determine whether genetic variation in Folh1 is contributing to effects on folate metabolism and blood pressure in the SHR compared with the SHR.BN-chr.1 congenic strain. Knockout of Folr1 in the mouse is embryonically lethal, 25 and the effects of genetic variation in Folr1 expression on blood pressure and metabolic traits in mice remain to be determined. Partially rescued preterm Folr1 −/− fetuses were found to have outflow tract defects, aortic arch abnormalities, and isolated dextrocardia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Thus, further studies will be of interest to determine whether genetic variation in Folh1 is contributing to effects on folate metabolism and blood pressure in the SHR compared with the SHR.BN-chr.1 congenic strain. Knockout of Folr1 in the mouse is embryonically lethal, 25 and the effects of genetic variation in Folr1 expression on blood pressure and metabolic traits in mice remain to be determined. Partially rescued preterm Folr1 −/− fetuses were found to have outflow tract defects, aortic arch abnormalities, and isolated dextrocardia.…”
Section: Discussionmentioning
confidence: 99%
“…Partially rescued preterm Folr1 −/− fetuses were found to have outflow tract defects, aortic arch abnormalities, and isolated dextrocardia. 25 To the best of our knowledge, no metabolic traits were studied in these mice.Although the exact relevance of folate metabolism in the SHR model to pathogenesis of metabolic syndrome in humans requires additional study, several lines of evidence strongly suggest that folate deficiency plays a role in at least some features of metabolic syndrome in humans. There is epidemiological evidence showing decreased folate levels or low folate intake to be associated with increased risk of cardiovascular disease and hypertension in humans.…”
mentioning
confidence: 99%
“…It would not be surprising to learn that folate could modulate gene expression also via association with a nuclear form of the folate receptor. [20][21][22][23] Several lines of evidence suggest that the high-affinity folate receptor may contribute to the malignant phenotype. 24 First, the known biologic function of the folate receptor is to supply folates for the biosynthesis of nucleotide bases and the methylation of isoprenylated proteins such as ras.…”
Section: Discussionmentioning
confidence: 99%
“…Results from another of the laboratories collaborating in this study showed multiple developmental abnormalities related to the massive die-off of neural tube and neural crest cells in Folbp1À/À (Folr1À/À) knockout mouse (Piedrahita et al, 1999;Zhu et al, 2007), damage that was far more extensive than is the case for the current study. These contrasting results demonstrate a difference between the global loss of Folbp1 and its reduced expression in a highly focused spatiotemporal manner.…”
Section: Discussionmentioning
confidence: 48%
“…Recent evidence reported by members of this research team indicate that abnormal expression of folate receptor genes in the mouse embryo model is associated with abnormal development of the heart and other neural tube-or neural crest-derived structures (Zhu et al, 2007;Taparia et al, 2007). Furthermore, Saitsu et al (2003) demonstrated that the expression of the folate receptor Folbp1 (also called Folr1, which is homologous with human Folr1 [FRalpha] and avian Folr1) was expressed at high levels in the dorsal neural tube during neural crest formation, indicating its potential role in neural crest development.…”
Section: Introductionmentioning
confidence: 99%